Developmental Table and Three-Dimensional Embryological Image Resource of the Ascidian Ascidiella aspersa - Funakoshi, Haruka M.; Shito, Takumi T.; Oka, Kotaro; Hotta, Kohji (Frontiers in Cell and Developmental Biology, 2021)
Ascidiella aspersa is an ascidian in the class of chordates—the closest relatives of vertebrates. A. aspersa is a potential model organism for bio-imaging studies due to its extremely transparent embryos as well as is a globally distributed cosmopolitan species. However, there is no standard developmental table for this organism. Here, as a first step to establish A. aspersa as a model organism, we report a standard developmental table as a web-based digital image resource. This resource used confocal laser scanning microscopy to scan more than 3000 cross-sectional images and 3D-reconstructed images of A. aspersa embryos during embryogenesis. With reference to the standardized developmental table of Ciona intestinalis type A, 26 different developmental stages (Stages 1 to 26) from fertilized eggs to hatched larvae were redefined for A. aspersa. Cell lineages up to the cleavage period were annotated: The cleavage patterns, the embryonic morphology, and the developmental time were then compared with Ciona. We found that the cleavage patterns and developmental time up to the neurula period in A. aspersa were extremely conserved versus Ciona. The ratio of the trunk and tail length in the tailbud period were smaller than Ciona indicating a relatively short tail. In addition, the timing of the bending of the tail is earlier than Ciona. This A. aspersa standard 3D digital resource is essential for connecting different omics data to different spatiotemporal hierarchies and is useful for a system-level understanding of chordate development and evolution.